THE ROLE OF LEADERS IN STRATEGIC MANAGEMENT FOR ORGANIZATIONAL SUCCESS - Supunpong, Worraseth; Somkong, Komsan; Tharathueke, Boonsan (Journal of MCU Nakhondhat, 2025)
This article aims to present ideas about the role of leadership in connection with strategic management for organizational success. From document review It was found that the roles of leadership and strategic management have roles and methods that are related in pairs as follows. Pair 1 Vision setting and strategy analysis in setting the vision and analyzing the strategy, the leader who sets the vision must use information from the organization’s strategy analysis, which includes an analysis of the external and internal context of the organization. The leaders of each department must work together to be analysts for the organization. Pair 2: Analytical thinking and strategy determination. In this step, when the organization has clearly defined the strategy that will be used. Leaders in each department must take that strategy and analyze it together with the missions of each department. To create a work plan at the agency level within the area that is properly supervised under the conditions real limitations. Couple 3: Creating motivation and putting strategies into practice. In putting the organization’s strategy into practice, it depends on the leaders of each department to motivate practitioners to see their own value and potential. The ability to create motivation is a special ability that is unique to a person. Potential leaders will have this characteristic. Pair 4: Assigning work and evaluating and controlling strategies. When leaders in each department create motivation for operators to see their own importance and the importance of work, then the organization needs leaders to evaluate and control strategies to meet goals.